Chlorhexidine for the Prevention of Omphalitis in neonates with a single dose - Muhammad Ishaq, Bilal Noor, Abdul Ahad, Naveed Muhammad, Romana Bibi, Sijad-Ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Worldwide, 44% (2,761 million) of the 6 million children who died before the age of five in 2013 did so during the newborn period. Globally, the first week of life is when 75% of newborn fatalities occur. Low-middle income nations account for 99% of newborn death worldwide. A great proportion of these neonatal deaths can be prevented if effective health measures are undertaken during birth giving prime importance to hygiene. Aim: To evaluate the effectiveness of a single application of chlorhexidine in the prevention of Omphalitis in neonates. Methodology: This randomised control experiment was carried out between October 2021 and April 2022, in the paediatrics unit of the Hayatabad Medical Complex in Peshawar. In this study, a total sample size of 64 with 32 in each group was observed. Newborn infants were randomly assigned to two types of cord care regimes, Group-A and Group-B. In Group-A newborns, the umbilical cord was cleansed with a single application of 4% chlorhexidine solution, and newborns in Group-B were instructed to leave the cord dry. The outcome of the study was the presence or absence of Omphalitis for which follow-up was done by the researcher on days 7th, 14th, 21st, and 28th of life in the hospital or through a home visit, whichever was acceptable to parents. The outcome measurement was recorded through proforma. Results: In this study mean age in Group A was 7± 2.77 days. Whereasthe mean age in Group B was 7±3.12 days. In group-A Fifty-six percent of neonates were male and 44% of neonates were female. Whereas in Group B 53% of neonates were male and 47% of neonates were female. 94% of patients responded favourably to additional chlorhexidine solution, whereas 6% did not..whereas Group B dry cord was successful in preventing Neonatal Omphalitis in 78% of cases and failed in 22% of individuals. Practical implication: With the use of chlorhexidine in newborn prevent neonates from sepsis and reduce mortality and morbidity. Conclusion:Our study concludes that a single application of chlorhexidine is more effective than a dry cord in the prevention of Omphalitis in neonates. Keywords: effectiveness, a single application of chlorhexidine, Omphalitis, neonates.